Development of a Web-Based Selling System Utilizing the RajaOngkir API at Toko Hijab ByAlya to Enhance Online Transaction Performance - Safitri, Sabrina Alya; Wijayanti, Esti; Chamid, Ahmad Abdul (Journal La Multiapp, 2025)
Toko Hijab By Alya, located in Kudus, is a newly established hijab retail store that faces challenges in reaching potential customers who do not use mobile-based e-commerce applications. To address this issue, a web-based selling system has been developed, integrated with the RajaOngkirAPI. This system allows customers to conveniently purchase hijab products online without the need to install additional applications, while simultaneously providing real-time and accurate shipping cost estimations. The integration of the RajaOngkir API enables the calculation of shipping fees from various courier services, enhancing transparency and improving customer satisfaction regarding delivery charges. The web-based platform not only simplifies the shopping experience but also provides clear and accessible delivery information, enabling the store to expand its market reach and increase online transaction volume. The implementation of this system is expected to significantly improve online sales performance and provide customers with a seamless shopping experience.